2022
DOI: 10.3311/ppci.18701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Saturation on the Ultrasonic Pulse Velocities of Different Stones

Abstract: Water saturation is considered one of the major factors influencing stones deterioration. The effect of moisture on the deterioration process of stone was investigated with the help of ultrasonic wave velocities. P and S waves velocities were calculated for twelve different lithotypes including limestone (porous limestone, laminated and less-laminated travertine, cemented limestone), sandstone and basalt. Water saturation tests were carried out based on the standard procedure of EN 13755. With the help of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…He discovered a linear relationship: the Poisson's ratio of the rock mass (ν rm ), which measures the quality of the rock mass, rises as the rock mass's geological strength index, or GSI, declines. Besharatinezhad et al [48] studied the effect of GSI and Poisson's ratio of the intact rock (ν i ) on the critical height of vertical rock mass slope. They concluded that as Poisson's ratio of the intact rock (ν i ) decrease, the critical height of vertical rock mass slope increases [48].…”
Section: Poisson's Ratio In the Function Of The Geological Strength I...mentioning
confidence: 99%
See 1 more Smart Citation
“…He discovered a linear relationship: the Poisson's ratio of the rock mass (ν rm ), which measures the quality of the rock mass, rises as the rock mass's geological strength index, or GSI, declines. Besharatinezhad et al [48] studied the effect of GSI and Poisson's ratio of the intact rock (ν i ) on the critical height of vertical rock mass slope. They concluded that as Poisson's ratio of the intact rock (ν i ) decrease, the critical height of vertical rock mass slope increases [48].…”
Section: Poisson's Ratio In the Function Of The Geological Strength I...mentioning
confidence: 99%
“…Besharatinezhad et al [48] studied the effect of GSI and Poisson's ratio of the intact rock (ν i ) on the critical height of vertical rock mass slope. They concluded that as Poisson's ratio of the intact rock (ν i ) decrease, the critical height of vertical rock mass slope increases [48].…”
Section: Poisson's Ratio In the Function Of The Geological Strength I...mentioning
confidence: 99%
“…The ultrasonic pulse velocity test is a non-destructive method to evaluate the physical and mechanical properties of different soils and rocks [32,33]. In the present study, it was conducted using the PUNDIT device (Portable Ultrasonic Non-destructive Digital Indicating Tester) based on the ASTM C597.…”
Section: Ultrasonic Pulse Velocity Testingmentioning
confidence: 99%
“…However, obtaining samples with the appropriate geometry and quality from jointed rocks is a challenging task, making it difficult to prepare suitable samples. Therefore, prediction models have been developed based on physical characteristics and wave velocity [1,2]. Numerous studies have been performed by various researchers to estimate the geo-mechanical properties in dry and saturated conditions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%